Análise dos efeitos da ingestão da polpa de juçara (euterpe edulis mart) sobre a atividade física espontânea e homeostase energética de camundongos alimentados com dieta hiperlipídica - Barthichoto, Marcela [UNIFESP] (2016)
Introduction: Obesity is considered a major public health issue, associated with metabolic, inflammatory and hemodynamic abnormalities. On the other hand, the consumption of proper amounts of fruit and vegetables with antioxidant properties lowers the risk for developing non-communicable chronic diseases. The fruit of juçara palm is rich in flavonoids, specifically anthocyanins, compounds with antioxidant and anti-inflammatory properties, which has also been shown to improve insulin sensitivity and reduce weight gain. Objective: Characterize the effect of juçara intake (Euterpe edulis Mart.) on energy homeostasis, spontaneous physical activity and glucose homeostasis in mice fed with high-fat diet. Methods: C57BL/6 mice were divided into 4 groups, according to the diet they received during 16 weeks: control diet (C), control diet supplemented with 0,5% juçara (CJ), high-fat diet (H) (34% fat) and high-fat diet supplemented with 0,5% juçara (HJ). Food intake, energy expenditure, feed efficiency, metabolic efficiency, spontaneous physical activity, glucose tolerance and insulin sensitivity (glucose and insulin tolerance test, respectively), brown adipose tissue UCP-1 protein expression and histopathologic analysis of the liver were analyzed. Results: Weight gain was higher in groups fed with high-fat diet (H and HJ > C and CJ). Supplementation with juçara increased weight gain in the control group (CJ> C), but decreased in high-fat group (HJ< H). Caloric intake (kcal/day) was higher in high-fat groups (H and HJ > C and CJ) and lower in juçara groups (CJ< C; HJ < H) in the first week. However, at 30, 60, 90 and 120 days, the intake was higher in the CJ compared to the C group, with no difference between H and HJ. Metabolic efficiency was lower and feed efficiency was higher in high-fat groups (H and HJ < C and CJ). Also, feed efficiency was higher in H than HJ, with no difference between C and CJ. Juçara increased energy expenditure in the high-fat group (HJ > H), but no differences were found in brown adipose tissue UCP-1 protein expression between H and HJ. There was no change in locomotor activity. High-fat diet decreased glucose tolerance and insulin sensitivity (H and HJ < C and CJ), but juçara improved sensitivity to this hormone (HJ > H). Juçara supplementation also reduced hepatic steatosis caused by high-fat diet (HJ < H). Conclusion: In mice fed high-fat diet, supplementation with juçara had important benefits: reduced weight gain, increased energy expenditure, improved insulin sensitivity and reduced hepatic steatosis. Spontaneous physical activity was not affected by high-fat diet or by juçara. In contrast, for mice fed with control diet, the juçara pulp resulted in greater weight gain, due to increased caloric intake.